2012
DOI: 10.1158/1078-0432.ccr-12-0406
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Tumor VEGF-A Levels with 89Zr-Bevacizumab PET as an Early Biomarker for the Antiangiogenic Effect of Everolimus Treatment in an Ovarian Cancer Xenograft Model

Abstract: Purpose: The mTOR pathway is frequently activated in ovarian cancers. mTOR inhibitors, such as everolimus, can reduce VEGF-A production by cancer cells. We investigated whether early everolimus treatment effects could be monitored by positron emission tomography (PET) with 89Zr-bevacizumab. Experimental Design: The effect of everolimus on VEGF-A secretion was determined in a panel of human ovarian cancer cell lines and in A2780luc+ ovarian cancer cells xenografted subcutaneously in BALB/c mice. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 37 publications
(50 reference statements)
3
29
0
Order By: Relevance
“…We showed that everolimus lowered 89 Zr-bevacizumab uptake in an ovarian cancer xenograft model and coincided with lowered tumor VEGF-A levels (16). Moreover, this approach is feasible in patients.…”
mentioning
confidence: 70%
“…We showed that everolimus lowered 89 Zr-bevacizumab uptake in an ovarian cancer xenograft model and coincided with lowered tumor VEGF-A levels (16). Moreover, this approach is feasible in patients.…”
mentioning
confidence: 70%
“…89 Zr-labeled bevacizumab PET imaging may help in assessment of the inter-and intrapatient heterogeneity of drug biodistribution in vivo, thereby predicting the presence or absence of a response in patients subsequently treated with bevacizumab. Studies in both mice and adult patients confirmed that 89 Zr-bevacizumab PET imaging was feasible and able to reveal bevacizumab accumulation in VEGF-positive tumors (7,(12)(13)(14). In addition, in adult renal cancer tumors, 89 Zr-bevacizumab uptake was correlated with a response to bevacizumab treatment (13).…”
mentioning
confidence: 77%
“…These postinjection times were based on previous research in mice and clinical studies in adults with 89 Zr-bevacizumab (7,12,14). The production and purification of 89 Zr and its coupling to bevacizumab were performed in accordance with good manufacturing practice at VU University Medical Center.…”
Section: Study Populationmentioning
confidence: 99%
“…VEGF/VEGFR antibodies have been labeled with various radioisotopes for the imaging of VEGFR expression in various disease models (20). For example, extracellular VEGF imaging was accomplished by coupling anti-VEGF monoclonal antibodies (bevacizumab, HuMV833) with 89 Zr (21,22), 111 In (23), and 124 I (24). Recombinant VEGF 165 was efficiently labeled with 123 I and VEGF 121 with both 99m Tc and 64 Cu for VEGF imaging in preclinical models (25)(26)(27)(28).…”
mentioning
confidence: 99%